Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Digital Marketing Terhadap Loyalitas Pelanggan 24ever coffee - Rahma, Alma Syifa; Putri, Fuzha Melyani; Khomairo, Ratu Dini; Zulaieka, Almira; Sialagan, Demak (Universitas Mercu Buana, 2025)
This study aims to determine the effect of product quality, service quality, and digital marketing on customer loyalty at 24ever Coffee. The research used a quantitative approach with a case study design. Data were collected using a questionnaire distributed to 60 respondents through social media, using a Likert scale. The study employed multiple linear regression analysis with SPSS and included classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The results of the study show that product quality and digital marketing have a significant positive effect on customer loyalty, while service quality does not show a significant effect. The findings suggest that to improve customer loyalty, 24ever Coffee should prioritize enhancing product quality and utilizing digital marketing strategies effectively. Although service quality did not significantly influence loyalty in this study, it still remains important to support overall customer satisfaction. These insights are expected to guide strategic decisions for businesses in maintaining competitiveness and sustaining customer relationships.